Effect of a halo-type structure on neck muscle activation of an open-cockpit race car driver training under qualifying conditions - Rosalie, Simon; Malone, J. (British Medical Journal Publishing Group, 2018)
The Fédération Internationale de l'Automobile recently mandated the use of the halo frontal cockpit protection system to mitigate the risk of impact to the driver's head. Here we describe the effect of a halo-type structure on the neck muscle activity of one of the authors, who is a national-level amateur racing driver, during a full qualifying session. We found that the workload of sternocleidomastoid increased and the workload of cervical erector spinae decreased with the halo fitted which is indicative of a forward head position. Left sternocleidomastoid and right cervical erector spinae fatigued more rapidly; whereas, left cervical erector spinae fatigued more slowly. There was no change in the rate of fatigue of right sternocleidomastoid. In combination with a forward head position, this suggests an increase in lateral flexion during head rotation which may affect accuracy of navigation. Thus, drivers may need to be trained to adapt to the halo to mitigate the effects on head position and movement.